Does Social Support Predicts a Person's Quality of Life? - Onn, P. P.; Teoh, H. J.; Sinniah, D.; Pillay, S. K.; Kannan, K. (ANIMA Indonesian Psychological Journal, 2006)
The purpose of this study is to examine whether social support predicts a person's quality of life. Seventynine adults between the ages of 18 to 55 year-old participated in this study. Subjects were required to complete 2 sets of questionnaires consisting of "The Social Support Questionnaires" and " Comprehensive Quality of Life Scales for Adults". The finding was congruent with the prediction where by social support does predict a person's quality of life. Kajian ini bertujuan untuk mengetahui apakah dukungan sosial dapat meramalkan kualitas hidup seseorang. Tujuh puluh sembilan orang dewasa berusia di antara 18 hingga 55 tahun telah berpartisipasi dalam kajian ini sebagai sampel. Subjek melengkapi dua perangkat kuesioner yang berisi "The Social Support Questionnaire" dan "Comprehensive Quality of Life Scales of Life Scales for Adults". Temuan kajian menunjukkan keterkaitan dengan dugaan bahwa dukungan sosial mampu meramalkan kualitas hidup seseorang.